The effect of age, sex and strains on the performance and outcome in animal models of stroke. (July 2019) - Zhang, Hongxia; Lin, Siyang; Chen, Xudong; Gu, Lei; Zhu, Xiaohong; Zhang, Yinuo; Reyes, Kassandra; Wang, Brian; Jin, Kunlin
Abstract: Stroke is one of the leading causes of death worldwide, and the majority of cerebral stroke is caused by occlusion of cerebral circulation, which eventually leads to brain infarction. Although stroke occurs mainly in the aged population, most animal models for experimental stroke in vivo almost universally rely on young-adult rodents for the evaluation of neuropathological, neurological, or behavioral outcomes after stroke due to their greater availability, lower cost, and fewer health problems. However, it is well established that aged animals differ from young animals in terms of physiology, neurochemistry, and behavior. Stroke-induced changes are more pronounced with advancing age. Therefore, the overlooked role of age in animal models of stroke could have an impact on data quality and hinder the translation of rodent models to humans. In addition to aging, other factors also influence functional performance after ischemic stroke. In this article, we summarize the differences between young and aged animals, the impact of age, sex and animal strains on performance and outcome in animal models of stroke and emphasize age as a key factor in preclinical stroke studies. Highlights: Age is a crucial factor in preclinical stroke studies. One can easily translate rodent age in months to human age in years. There exist distinct physiological differences between normal young, and old animals. .Rodents are commonly used in stroke research followed by non-human primates and canines. Sex and strain differences are major factors affecting stroke outcome.